'The Signature of Architecture': Compositional Ideas in the Theory of Profiles. Issue 1 (6th November 2015) - Hill, Michael; Kohane, Peter
Abstract : The theory of profiles from the fifteenth to the nineteenth century is subtly distinct from the theory of the architectural orders. Francesco di Giorgio initiated the topic with his analogy of cornice and facial profiles. Michelangelo further exploited the conceit, while also developing the formal, particularly skiagraphical, potential of mouldings. In the seventeenth century, Vincenzo Scamozzi set the archaeological findings of architects into a framework of rhetoric, which furnished terms for formal analysis, audience reception, and ornamental affects. Rhetoric also encouraged profiles to be understood in terms of symmetry and decorum, so that the composition befitted its place within the genre of the order and the building. If the rhetorical model was applied to profiles, it could also be applied to architecture as a whole, in which case profiles were the equivalent to the rhetorical category of elocutio, which was the context for Boffrand's treatment of profiles in the eighteenth century. And if profiles spoke, they could have character, as Jacques François Blondel would so famously demonstrate soon after. In contrast, William Chambers saw mouldings in terms of the expression of weight, an idea so appealing to Francesco Milizia that he copied Chambers's entire account of the topic into his own Principii . Chambers's implicit structural rationalism, however, was not so much a message from the future as a statement of the desirability of coherence, with each part performing its allotted role, in keeping with the rhetorical principle that expression must both fit together and be fitted to its purpose. The paper argues that rather than being minor details, mouldings encapsulated wider theories of expression — 'the signature of architecture'.